Peran Kepolisian Dalam Penanganan Tindak Pidana Pencurian Uang Dengan Modus Skimming (Studi di Polda Sumatera Utara) - Sihaloho, Jessica Angelin; Zulyadi, Rizkan; Isnaini, Isnaini (JUNCTO: Jurnal Ilmiah Hukum, 2024)
Skimming crime is an act of stealing credit or debit card information by illegally copying information contained on the magnetic stripe of a credit or debit card. Generally, skimming criminals in carrying out their actions, perpetrators put a skimmer device on an ATM machine where this tool is useful for duplicating data from the victim's ATM. The type of legal research is juridical normative with conceptual approach methods and legislation with instruments of collecting observational data, documentation studies and interviews. The data analysis is descriptive analytical. In its role, the Police has a very important position to overcome and handle and conduct investigations and investigations of theft using skimmers. Various tasks that have been tried by the Cyber Sub-Directorate of the North Sumatra Police in tackling the crime of money theft using skimmers are in accordance with applicable regulations in Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia. Police efforts are an integral part of social policy. The victim suffered a reported loss of theft and duplication of data (skimming) without the knowledge and consent of Bank Sumut (victim) and suffered a loss of +/- Rp. 4,700,000,000-, (four billion seven hundred million rupiah), then the victim made a report on the incident to the SPKT POLDA SUMUT, so that the reported person could be processed.